Lessons Learned in Dealing with Large-Scale Disasters - Hutchison, Daniel (Assurances et gestion des risques / Insurance and Risk Management, 2005)
Many OECD countries have been affected by major harmful events in recent years. The considerable human and economic costs of such events and the repercussion they might have for the global economy have become recurring causes for concern. Given its intergovernmental and multidisciplinary nature, and its experience in risk and disaster management in a variety of fields, the OECD is well positioned to analyse the impact of major disasters on societies and economies, and to identify optimal practices in response and recovery phases. To this end, the OECD’s International Futures Programme supervised a team of specialists from eight OECD directorates, and a team of Turkish specialists who provided the material for chapter 3. The report was prepared between May and July 2003. This report analyses the economic and social impacts of recent large-scale disasters, and draws some initial lessons for the monitoring and the management of future disasters. The report primarily focuses on restoring trust and securing recovery after a major harmful event has occurred. The events reviewed are as diverse as the Chernobyl nuclear accident, the Kobe and Marmara earthquakes, Hurricane Andrew, and the 11th September terrorist attacks on New York and Washington. Disasters such as these have in common massive effects on large concentrations of people, activity and wealth. They disrupt multiple vital Systems such as energy supplies, transport and communications. Their effects spread beyond the region originally affected and generate widespread anxiety. In some cases, the public expresses distrust of the ability of governments to protect citizens.